An empirical analysis of factors influencing the adoption of Mobile Instant Messaging in China. (5th October 2011) - Jiang, Guoyin; Deng, Wenjuan
This paper derive a theoretical model from Technology Acceptance Model (TAM) and social network theory to empirically elaborate how factors can effect on users' adoption of Mobile Instant Messaging (MIM). Based on an online and off-line survey data from a sample of 364 Chinese MIM users, structural equation model to analyse why Chinese users adopt MIM. The study reveals that social and technical factors significantly affect users' adoption of MIM. Perceived Usefulness (PU) is the most influential part in user's attitude towards using MIM, followed by Perceived Entertainment (PE), cross-platform interaction and Perceived Ease Of Use (PEOU); perceived Synergy Value (SV) significantly affects PU and ease of use, while cross-platform OS and cost have negatively correlation with individual's attitude. Implications for formulating business strategies so as to improve MIM product and customer service, and suggestions for future research are provided.